Constructivist Model of Inclusive Education for Forming Students’ Tolerance in Pondok Modern Darussalam Gontor - Syarifah Syarifah; Maskuri Maskuri; Junaidi Mistar (AS-SABIQUN, 2026)
The persistence of intolerance in society underscores the critical role of education in shaping tolerant attitudes, particularly within faith-based educational settings. This study aimed to analyze the constructivist approach in inclusive education and its implications for the formation of tolerant attitudes among students at Pondok Modern Darussalam Gontor. A qualitative approach with an ethnographic design was employed, with data collected over the course of one year through participatory observation, in-depth interviews, and document study. Data were analyzed interactively through the stages of data reduction, data display, and conclusion drawing. The findings show that inclusive education at Pondok Modern Darussalam Gontor is implemented through the shared life of students from diverse cultural, regional, and character backgrounds within a unified schooling and boarding system. The constructivist approach is manifested in learning and student development processes that position students as active subjects in constructing their understanding and tolerant attitudes through direct experience, social interaction, collaborative work, and reflection. Tolerance education is carried out through two models, namely direct tolerance and indirect tolerance, which operate integratively within the framework of inclusive education, thereby making tolerance not merely a norm but a consciously internalized character within the students. The study concludes that a constructivist approach within inclusive education is effective in fostering students’ tolerant attitudes in an active, reflective, and sustainable manner, and affirms that Islamic boarding schools hold strategic potential as character education spaces capable of preparing students to live harmoniously in a plural society. Keywords: Constructivist Learning; Inclusive Education; Development of Tolerance; Islamic Boarding Schools; Character Education